Diverging Perspectives: A Qualitative Study of How Physicians and Informal Caregivers Perceive End-of-Life Communication - Emily S. Schuler; Nashell Wilson; Sarah E. Koch; Zheng Lian; Kafayat Mahmoud; Clifford Ross; Zhe Zhang; Benmun Damul; Brina Ratangee; Deborah Carr; Elizabeth A. Luth; Lucie Kalousová (American Journal of Hospice and Palliative Medicine®, 2026)
Introduction Patients often express a desire to discuss their end of life with physicians, yet patient-provider communication regarding this topic is often poor. Insufficient communication may prevent dying older adults from receiving care that aligns with their preferences. Physicians and informal caregivers may assess the quality of their end-of-life communications differently; however, it is unclear whether these misalignments undermine their quality of care. Methods We conducted semi-structured focus groups with 19 physicians who routinely provide end-of-life care and 21 recently bereaved informal caregivers of older adults. We analyzed transcripts using an inductive, line-by-line coding approach to generate themes grounded in participant experiences. Results We identified two overarching themes highlighting differences in physician and caregiver perspectives regarding end-of-life communication: roles and responsibilities; and perceived barriers to end-of-life planning. Physicians attributed ineffective communication to patients’ poor health literacy, and felt that in-depth end-of-life planning conversations were outside their scope of practice. Bereaved caregivers attributed poor communication to their fear of challenging medical authority, and limited information exchange with physicians. Physicians emphasized financial barriers to end-of-life planning, whereas caregivers emphasized their unmet needs for physician guidance. Conclusions Physicians and bereaved caregivers differed in how end-of-life communication is experienced, evaluated, and acted upon, which exacerbated pre-existing informational barriers for caregivers and created an additional obstacle to achieving goal-concordant care. Physicians’ overestimation of patients’ baseline end-of-life knowledge coupled with caregivers’ unaddressed informational needs and difficulty challenging medical authority at the end of life may limit the quality and delivery of end-of-life care that aligns with patient preferences.